A Study on Indian Mutual Fund Industry and Its Nature: Evolution and Current State of the Indian Mutual Fund Industry (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Mutual Funds have been a significant sourceof investment in both government and corporate securities. It has been for thedecades the monopoly of the state with UTI being the key player with investedfunds exceeding Rs. 300 bn. (US $ 10 bn.). The state owned insurance companiesalso hold a portfolio of stocks. Presently, numerous mutual funds exist,including private and foreign companies. Banks - mainly state owned too haveestablished Mutual Funds (MFs). Foreign participation in mutual funds and assetmanagement companies permitted on a case-by-case basis.